Bacterial flora of chronic venous leg ulcers: shifts over a two-decade period - Matić, Mian; Matić, Aleksandra (Vojnosanitetski pregled, 2025)
Background/Aim. Venous leg ulcers (VLUs) are often colonized by various types of bacteria, which can lead to infection that requires empirical antibiotic therapy. Bacterial types and their antibiotic susceptibility vary widely over time and by geographic location. The aim of the study was to determine the change trends of causative bacteria and antibiotic susceptibility in patients with VLUs over the past two decades. Methods. The study was conducted at a tertiary care dermatovenereology clinic. Data on the microbiological analysis of ulcer swabs from patients with VLUs were collected over two consecutive months at three time points: 2001, 2014, and 2020. Results. The study included 250 patients divided into three groups. The first group (2001) had 111 participants, the second group (2014) had 64, and the third group (2020) had 75 participants. Out of the 250 swabs sent for microbiological testing, only 4 (1.6%) samples yielded negative results. In 2001, the bacteria identified were 31.83% Gram-positive (G+) and 68.13% Gram-negative (G-). In 2014, the ratio between G+ and G- bacteria was 27.18% vs. 72.82%. In 2020, the predominance of G- bacteria was even more pronounced, with 89.86% compared to 10.14% G+ (p < 0.001). In 2001, Pseudomonas (P.) aeruginosa (P. aeruginosa) (26.54%) was the predominant G- bacterium, and Staphylococcus (S.) aureus (24.78%) was the most common G+ bacterium. In 2014, P. aeruginosa (30.10%) and S. aureus (23.30%) remained prevalent. By 2020, P. aeruginosa (35.14%) increased further, while S. aureus (7.43%) decreased significantly (p < 0.001). Antibiotic sensitivity varied over the years, with older antibiotics showing decreased efficacy and newer classes demonstrating increased sensitivity. Conclusion. Throughout the study period, there was a notable shift toward G- bacterial dominance, particularly P. aeruginosa. Antibiotic resistance patterns also evolved. This study highlights the importance of local surveillance of bacterial flora of VLUs and antibiotic resistance profiles.